A multicomponent diffusion model for gas charges into oil reservoirs. (15th September 2016) - Pan, Shu; Zuo, Julian Y.; Wang, Kang; Chen, Yi; Mullins, Oliver C.
Abstract: Asphaltene expulsion appears to be an important mechanism in the formation of a heavy oil layer and/or a tar mat at the base of an oil column during gas charges. To better understand this dynamic process, a multicomponent diffusion model has been developed to simulate the diffusion during gas charge processes in oil reservoirs. In this model, a complex moving boundary diffusion problem has been converted into a fixed boundary problem with simple boundary conditions. The constitutive equations linking the diffusion fluxes to the concentration gradient are given under the framework of the non-equilibrium thermodynamics. All the required thermodynamic properties are obtained from the Flory–Huggins regular solution model. This model has been used to study the gas charge processes in a representative ternary hydrocarbon reservoir system through two case studies. The studies have demonstrated the occurrences of asphaltene expulsion and two different types of density inversion during gas charges. A type I density inversion originates from a synergy of the asphaltene expulsion and an impermeable bottom boundary. It results in a concentration profile with a big, flat asphaltene hump near the reservoir bottom. The predominant cause of a type II density inversion is asphaltene expulsion, and it can induce buoyancy convection, which may accelerate the asphaltene migration to the base of the column. When operative, buoyancy convection is far more efficient than diffusion for asphaltene redistribution.